Determination of Dissociation Constants of Malonic Acid in (Ethylene Glycol-Water)X% Mixed Solvent at Different Temperatures Using Electromotive Force Measurements - Ahmed, Soleen S.; Jamil, Lazgin A. (Science Journal of University of Zakho, 2019)
The first and second dissociation constants of malonic acid in different composition of (ethylene glycol-water)%, (10, 20 and 30)% mixed solvent determined using the electromotive force measurements of galvanic cells without liquid junction at nine different temperatures,  at  interval, including the body temperature. The value of the first and second thermodynamic dissociation constants have been used to determine the thermodynamic quantities of two dissociation processes. These quantities involved the standard free energy,  standard enthalpy change,  standard entropy change,  and standard heat capacity change.
Keywords: Electromotive force; Thermodynamic dissociation constant; Malonic acid; Ethylene glycol-water mixed solvent; thermodynamic quantity